2014
DOI: 10.3390/su6084858
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Sewage Charge Policies, Environmental Protection Industry and Polluting Enterprises—A Case Study in China

Abstract: Abstract:The game model of sewage charges, based on incremental mode, was developed. Four modes of high/low sewage charge standards were utilized to analyze the relationship between control strategy on sewage discharge and the development of environmental protection industry. Results showed that the selection of control strategy was heavily dependent on the level of sewage charges. An empirical study was carried out to investigate the environmental protection industry in 31 regions in China in 2010. It was rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Short-term regional cooperative pollution controls, such as “APEC Blue” and “Parade Blue,” are short-lived because they were promoted by short-term but strong intervention measures, such as shutting down polluters and traffic restriction, which is consistent with the results of previous studies (18, 2527).…”
Section: Discussionsupporting
confidence: 89%
“…Short-term regional cooperative pollution controls, such as “APEC Blue” and “Parade Blue,” are short-lived because they were promoted by short-term but strong intervention measures, such as shutting down polluters and traffic restriction, which is consistent with the results of previous studies (18, 2527).…”
Section: Discussionsupporting
confidence: 89%
“…The cost of treatment of heavy polluting enterprises such as the chemical industry and metal smelting is higher and worsens environmental degradation. Reducing the proportion of heavy industry can improve environmental efficiency by decreasing the consumption of energy and lead to economic dividends through resource utilization and technological progress [54]. However, the economic output brought by an increase in the heavy industry cannot make up for the social costs resulting from their environmental externalities [65].…”
Section: Empirical Results Of Didmentioning
confidence: 99%
“…The sewage charge system is the main system for the implementation of pollution control in China and represents the intensity of environmental regulation. It has been shown that the sewage charge system has improved environmental quality and achieved the goal of emissions reduction in recent years [53,54]. However, the effects are heterogeneous across regions.…”
Section: Emissions Trading System Effect Estimation: a Did Modelmentioning
confidence: 99%
“…From 2011 to 2030, the newly added hydropower, wind power, solar power and nuclear power will surpass 1 billion kW, in which nuclear power will occupy 15%-20% [36]. With the development of new energy, renewable energy and low-carbon energy, China will reduce the reliance on traditional fossil fuel and consequently improve the environmental performance, as well as the energy sustainability [56].…”
Section: Results and Discussion Of Lmdi Modelmentioning
confidence: 99%